Professional Development System of Elementary School English Teachers in Indonesia - Saragih, Orde Koria (Fakultas Ilmu Pendidikan Universitas Sari Mutiara Indonesia, 2018)
Indonesia has various teachers’ professional development programs from the pre-service English teacher up to in-service English teacher managed by the government in order to boost the teachers’ professional development effectively. In fact, English teachers particularly in the elementary level keep struggling in the terms of skill and knowledge. Therefore, by carrying out the literature review, this paper analyzed the current system and what is happening with the elementary English teacher in Indonesia. The results showed that the elementary English teachers’ professional development system in Indonesia is very well-planned and systematic, which starts from each teacher education institutions through their courses and continues to the PPG program. In the in-service program supervision, KKG, and PPGJ/ Certification are the three big programs which are mandated by the MOEC and MORA. It is also found that Indonesia has long process and tortuous certification program, powerful and rooted Professional Learning Communities (PLCs), non-independent teachers’ law, and unspecific pre-service education’ program. Even though not all of the teacher development programs in Indonesia are presented in this present study, the researchers suggest that there should be more specific program for the English elementary teacher in Indonesia’s pre-service education. It is also suggested to all educational practitioners in Indonesia and other Asian countries to form more professional learning communities (PLCs) since teachers can gain more knowledge through learning together